SISTEM INFORMASI KATALOG PERPUSTAKAAN DI PERGURUAN TINGGI DARMAJAYA - sri lestari (Jurnal Informatika, 2007)
Have been conducted a research of web based library information system development on-line at Darmajaya. At this time, Darmajaya`s Library has 4551 eks with 1993 titles, 86 eks Journal with 44 titles, 660 eks of final assignments,  186 eks of Skripsi and 443 eks of KP report, and this will be continued to increase along with the program of book levying coming from student. Donation and also form institution. At this time data of book`s catalogue at Darmajaya`s Library still using Microsoft Excel Application, and final assignment report data, skripsi, and KP report recorded at main book. This system, will have major influence with Darmajaya Library Services to members. With this Research Result can facilitate all library member to access the book information, Journal, KP report, Skripsi / Final Assigment, and GBPP through Internet. This Library Information System can improve Darmajaya Library services and represent one of place for the publication of scientific innovation / creation for all lecturer or student.